Leadership in education, corrections and law enforcement a commitment to ethics, equity and excellence - Normore, Anthony H.; Fitch, Brian D. (Advances in educational administration ;, 2011)
This volume fills a unique gap in the knowledge base the juncture between leadership, ethics, law, and how public institutions/organizations understand and practice the essence of all three. Authors from law enforcement, corrections education, and educational leadership present different yet overlapping constructs around ethics and law, and make an important step towards reconciling these differing views to demonstrate the significance of collaboration and partnerships for a common purpose. The volume develops a coherent theory on how multiple organizations can collaborate to gain 'public trust' for the 'greater good' of communities and society at large from the perspectives of law and ethics. Providing a broad-based view of the intersection where law and ethics meet leadership in multiple professions it sets the stage for the discussion of significance and timeliness of ethical behaviors and practices towards solving long lasting issues in education, corrections and law enforcement organizations. Implications for policy and practice are examined as well as creating an environment where the future discourse and direction of ethics and law in multiple organizations are discussed.